The civic reformation in Coventry, 1530-1580 - Carter, T (2012)
This thesis considers the civic elite in Coventry during the Reformation, from 1530-1580. It describes how the presence of a longstanding civic and political culture, dating back to the late middle ages, helped to mitigate religious change and bring other economic and social priorities to the fore during this period. The thesis looks at contemporary understanding of ideas of the city, including civic history and political power, as well as the economic forces which shaped the civic government?s interaction with other political hierarchies and the broader social world of the kingdom. It is argued that, although the corporation was keen to protect and define the political and physical boundaries of the city, they lived in an environment that was permeable to outside influence and the presence of geographically broad social and political networks. Urban political disputes are also examined, with the aim of elucidating those principles which ensured the smooth running of civic government and the control of the city by the corporation and the civic elite. Religious disagreements during the 1540s and 1550s are examined in detail, to show why, despite the potential for turmoil, the city never saw the breakdown of order or the political hierarchy. The spread of protestantism during later decades is dissected, alongside attempts to maintain urban religious provision at an acceptable standard, and to preserve the structures and hierarchies of civic religion. The thesis concludes that, even in cities like Coventry, where the effects of the dispute and dissonance that came with the growth of a new religion were strongest, it was possible for the traditional moral rules of urban governance to ensure that the city was an ordered and successful society well into the latter half of the sixteenth century.